The Acheloos painter - Moignard, E (1977)
The Preface enumerates the publications in which the Acheloos Painter is discussed by Beazley, from which it is clear that he thought of the painter as a member of the Leagros Group, but nonetheless distinct from them in having a humourous approach to his work which they lack. It is also suggested that from the point of view of the attribution of some of the vases more vaguely associated with the painter, it would be fruitful to pay attention to some of his own second-rate work. Chapter 1 describes the Acheloos Painter's graphic style, figure work, subsidiary patterns, and interest in foreshortening, and discusses his methods of composition. His use of two distinct head types is related to the contexts in which they appear. Some of the more loosely associated vases are attributed to five separate hands who relate closely to the Acheloos Painter, as does the Painter of Louvre F 314. Some new attributions are made to the Acheloos Painter himself, and his immediate stylistic background within the Leagros Group is discussed. A chronology based on his style is offered. Chapter 2 establishes a chronology based on the changes in pot shapes over the period of the Acheloos Painter's activity, and relates him to the painters with whom he shared a potter, which shows a clear pattern for his career. Chapter 3 offers a chronology conflating the charts based on style and potting. Chapter 4 compares the Acheloos Painter's choice of subjects and pairing of them on vases with more than one picture with the practice of the Leagros Group, the Pioneers, and the Antimenes Painter. The iconography of the Acheloos Painter's vases is discussed in detail subject by subject, and compared with other versions of the same subject by the Leagros Group and in earlier black figure. Chapter 5, the Conclusion, describes the Acheloos Painter's career and ethos on the basis of the evidence offered in the preceding chapters, and suggests that his interests were in the content of his pictures, and the two head types discussed in Chapter 1 were used for a specific purpose, whether political in intention or not. In any case, used in conjunction with an idiosyncratic iconography, they represent a deliberate dissociation from the practice of his workshop colleagues.